Activism and the Olympics : dissent at the games in Vancouver and London - Boykoff, Jules (Critical issues in sport and society., 2014)
"Shines a spotlight on the political underbelly of the Olympic Games. Because the Olympics have become such a multifaceted behemoth, they ramble into the path of numerous extant activist battles while spurring new ones. After presenting a brief history of political activism that challenges the Olympic Games, Boykoff turns his attention to the Vancouver 2010 Winter Olympics and the 2012 Summer Games in London. He argues that anti-Olympics activism is not so much a "movement of movements" as it is a "moment of movements." During the Olympics moment, activist groups come together using the Olympics as their fight-back focal point. But, he contends, anti-Olympics activism has not yet become a social movement, as it has not robustly sustained itself through time. Activists challenging the Games tend to deploy humor-based, with-the-grain tactics to create carnivalesque spectacles to challenge the Olympic machine. Boykoff offers a critical assessment of this approach"--